Service characteristics and the choice between exports and FDI: Evidence from Belgian firms - Leo Sleuwaegen; Peter M. Smith (National Bank of Belgium, 2020)
The decision to serve foreign markets through exports or foreign direct investment (FDI) has been studied within proximity-concentration models of location, mainly in the context of trade in goods. This paper adapts these models to account for the specific nature of services that are traded across borders. We show how services can be characterized by a bundle of attributes that collectively describe the service. These attributes are then tested to show how they affect the choice between exports and FDI using service-level data for firms in Belgium selling services abroad. Three different types of characteristic are shown to affect the export versus FDI decision: intangibility, the searchexperience-credence framework and the requirement for either the supplier or the client to physically move to the point of production.
Keywords: F14; M16; L8; 330; Services; International Trade; Exports; Foreign Direct Investment; Service characteristics